Spatial analysis of the neuronal fensity of aminergic brainstem nuclei in primary neurodegenerative and vascular dementia: a Comparative immunocytochemical and quantitative study using a graph method - Yang, Yan; Beyreuther, Konrad; Schmitt, Horst Peter (Analytical cellular pathology, 1999)
A graph method was employed to analyse spatial neuronal patterns of pontine nuclei with ascending aminergic projections to the forebrain (nucleus centralis superior (NCS), raphes dorsalis (NRD) and locus coeruleus (LC)), in Alzheimer disease (AD), Huntington disease (HD), and vascular (VD) as well as “mixed‐type” (VA) dementia, compared with non‐demented controls (CO) and a small sample of brains from schizophrenics (“dementia praecox” (DP)). The quantitative evaluations by the “minimal spanning tree (MST)” were complemented by rough neurofibrillary tangle (NFT) counts and by semiquantitative immunohistochemical assessment of amyloid deposition, neuritic plaque formation, and cellular gliosis. The AD cases showed a significant decline of neuronal density in all nuclei examined, as compared with controls and DP. Neuronal loss was not significant in VD, while the mixed cases with both vascular and Alzheimer‐type pathology exhibited pronounced changes of neuronal density. Amyloid deposition occurred almost exclusively in AD and VA, as a rule, being of moderate degree, except for two presenile AD cases where it was marked. NFT were significantly increased in all nuclei in AD and in the VA cases, while they only occasionally appeared beyond age 55 in HD, DP and CO. The four HD cases showed in the NCS and NRD neuronal loss as severe as in AD. This neuronal loss implicates impairment of serotoninergic and noradrenergic neuromodulation as one basic mechanism promoting dementia in AD, VA and perhaps in HD.